Створення етнографічних комплексів та експозицій як один з напрямів розвитку українського музейництва 1960-х – 1980-х років - Крук, О. (Краєзнавство, 2009)
У статті досліджується процес створення, функціонування в Україні етнографічних комплексів та експозицій протягом 1960-х — 1980-х років. В статье исследуется процесс создания, функционирования в Украине этнографических комплексов и экспозиций в течение 1960-х — 1980-х годов. The article deals with the investigation concerning a forming process of ethnographic complex and exposition for the period of 1960s — 1980s.
The author’s idea is: at that time museum establishments were actively developed involved in discovering, investigating and popularizing unique relics of material and spiritual culture.
The members of Ukrainian Society for Protection of Historical and Cultural Monuments played a vital role in establishing and arranging work of ethnographic museum complex. They took an active part in carring out search expeditions and other important research activities.
Due to joint efforts of Ukrainian National Academy of Sciences and outstanding ethnographers existence and functioning of museums became possible.
In the period of totalitarian system and Russian language domination the development of ethnographic museum resulted in preserving national self-consciousness and reborn peoples interest to their history and culture.